First peripheral drug-eluting stent clinical results from China: 1-year outcomes of the Zilver PTX China study - Ye, Wei; Böhme, Tanja; Fu, Weiguo; Liu, Changwei; Zhang, Xiaoming; Liu, Peng; Zhang, Jiwei; Zou, Yinghua; Lu, Xinwu; Lottes, Aaron E.; O'Leary, Erin E.; Zeller, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose: The benefit of using the Zilver PTX drug-eluting stent (DES) in superficial femoral artery (SFA) lesions has been demonstrated in multiple clinical studies. This prospective, multicenter study evaluated the 1-year safety and effectiveness of the DES for the treatment of femoropopliteal lesions in a Chinese patient population. Methods: Patients with a single de novo or restenotic SFA lesion ≤140mm and a Rutherford classification of 2 to 4 were treated with the DES. The primary endpoint was primary patency assessed by duplex ultrasound at 1 year. Secondary endpoints included adverse events, event-free survival (EFS), freedom from target lesion revascularization (TLR). Clinical outcomes included Rutherford classification, ankle-brachial index (ABI), and the walking impairment questionnaire (WIQ). Results: In this study, 178 patients with symptomatic peripheral artery disease were enrolled at nine institutions in China. The average lesion length was 79.0 ± 48.6mm (range 14.8-245.4mm) and 50.0% of lesions were total occlusions. The 1-year primary patency rate was 81.9%. A covariate analysis revealed that lesion length (p<0.01) was the only significant factor for patency. No paclitaxel-related adverse events or amputations were reported. The 1-year rate for EFS was 94.9% and freedom from TLR was 95.5%. Through 1 year, treatment with the DES resulted in statistically significant improvement in ABI and WIQ scores compared with pre-procedure (p<0.001). Clinical improvement of at least 1 Rutherford class was achieved in 142 of 174 patients (81.6%). Conclusion: This study showed promising short-term results for the treatment of SFA lesions with Zilver PTX DES in Chinese patients.